63.7k views
4 votes
3. If the function below (left) has a reflection about the "Y-AXIS", its new functionwould be below (right). *y=√xy = – VĩO TrueO FalseOther:

1 Answer

5 votes

The graph for the original function y=√x is:

And the graph for the new function y=-√x

As we can see, the reflection is about the x-axis, not the y-axis.

So, the Answer is FALSE.

3. If the function below (left) has a reflection about the "Y-AXIS", its-example-1
3. If the function below (left) has a reflection about the "Y-AXIS", its-example-2
User Jac
by
4.7k points